Synthesis and Anticonvulsant Activity of New N-(Alkyl/Substituted aryl)-N '-[4-(5-cyclohexylamino)-1,3,4-thiadiazole-2-yl)pheny]thioureas - KAYMAKÇIOĞLU, BEDİA; ARICIOĞLU, FEYZA; KARAKUŞ, SEVGİ (WILEY-V C H VERLAG GMBH, 2009)
A series of novel thiourea derivatives carrying the 5-cylohexylamino-1,3,4-thiadiazole moiety was synthesized and their anticonvulsant activity was evaluated. Structures of the synthesized compounds have been confirmed by IR, H-1-NMR, and elemental analysis. All of the compounds were administered at a dose of 50 mg/kg. Some of the active compounds have different effects in pentylenetetrazole (PTZ) and maximal electroshock (MES) tests, indicating the therapeutical potential in petit mal seizures, but not in grand mal seizures. Compounds 10, 11, 13, and 14 carrying 2-methylphenyl, 4-chlorophenyl, allyl, and 4-methylphenyl on the thiourea pharmacophore, increased the survival rate in the PTZ model. The ED50 values of the active compounds 10, 11, 13, and 14 were found 68.42, 43.75, 18.75 and 25 mg/kg, respectively.
Keywords: Anticonvulsant activity; Maximal electroshock seizure; Pentylenetetrazole; 1,3,4-Thiadiazoles; Thioureas; THIOUREA DERIVATIVES; IN-VITRO; HIV; DESIGN; AGENTS